2019
DOI: 10.2136/sssaj2019.05.0139
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregate Stability as Affected by Landuse and Soil Properties in the Lower Mississippi River Valley

Abstract: Core Ideas Improving soil aggregation may promote infiltration. Soil aggregation properties differ by land use. Grassland and forest restoration may improve groundwater recharge. Improving soil aggregate stability, thus improving infiltration and reducing surface runoff and soil erosion, may lead to multiple environmental benefits in the Lower Mississippi River Valley (LMRV). The objective of this study was to evaluate the effects of common landuses (i.e., native prairie, deciduous forest, coniferous forest, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…In the same line, AS was significantly lower in VINE and CROP, compared to FOR. This is also attributed to the conventional management applied, which is known to reduce AS [64][65][66]. The high BD and the reduced WHC, AFP, and AS imposed by intensive tillage and agrochemicals application are the causes for the significantly lower water infiltration in VINE and CROP than FOR.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, AS was significantly lower in VINE and CROP, compared to FOR. This is also attributed to the conventional management applied, which is known to reduce AS [64][65][66]. The high BD and the reduced WHC, AFP, and AS imposed by intensive tillage and agrochemicals application are the causes for the significantly lower water infiltration in VINE and CROP than FOR.…”
Section: Discussionmentioning
confidence: 99%
“…Soil aggregation is an important indicator of soil structural stability (Kalhoro et al., 2017; Sekaran et al., 2021; Six et al., 2000; Tourn et al., 2019) that influences soil health factors, including (a) soil organic C (SOC) conservation and nutrient dynamics (Rodríguez et al., 2021; Somasundaram et al., 2017; Weidhuner et al., 2021; S. Xu et al., 2021), (b) porosity and water retention (Regelink et al., 2015; Sekaran et al., 2021), (c) water infiltration and surface runoff, and (d) soil erosion (Anderson et al., 2019). Soil organic matter (SOM) is one of the major binding agent responsible for formation and stabilization of soil micro‐ (<250 μm) or macroaggregates (>250 μm) (Jastrow & Miller, 1998; Six et al., 1999; Tisdall & Oades, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that some soil quality and aggregate stability indices are changing with management and land-use types. Anderson et al [20] reported that means of MWD wet and WSA in coniferous forests and grasslands were significantly greater than the means of those properties in croplands, including conventional-tillage and no-tillage agriculture in the lower Mississippi river valley area. Tang et al [21] showed the importance of MWD dry , MWD wet , GMD dry , GMD wet , and WSA in the different types of land in the following order: woodland > grassland > shrub land > bare land.…”
Section: Physical and Chemical Properties Of Soils Under Different Land-use Typesmentioning
confidence: 99%
“…Recently, more attention has been paid to investigating the effects of land use changes on soil properties. Anderson et al [20] reported that the MWD wet and WSA in coniferous forests and grasslands were significantly higher than those in croplands, including conventional-tillage and no-tillage agricultures. Furthermore, in Calcisol Leptosols, China, Tang et al [21] reported the values of MWD dry , GMD dry , and WSA in the different land types in the following order: wood land > grassland > shrub land > bare land.…”
Section: Introductionmentioning
confidence: 99%